Price Adjustment under the Table - Daniel Levy (Handbook of Frauds, Scams, and Swindles: Failures of Ethics in Leadership, 2009)
Based on a first-hand account, this paper offers evidence on corrupt price setting and price adjustment mechanisms that were illegally employed under the Soviet planning and rationing regime in the USSR. The evidence is anecdotal, and is based on personal experience during the years 1960–1971 in the Republic of Georgia.
Keywords: B14; D30; D73; E64; H26; H40; K42; O17; P20; P26; Z13; 330; Corruption; Black Market; Bribe; Price System; Distorted Relative Prices; USSR; Command Economy